Landscape composition and proximity to water structure American badger (Taxidea taxus) distributions in shortgrass prairies - Piper, Colleen Whitney (Kansas State University, 2021)
Widespread land-use changes in the Great Plains have resulted in a patchy mosaic of prairie embedded within human-modified landscapes. The distribution of prairie-obligate species in this region may be constrained by these alternate land-use types, though many carnivore-specific examples are unknown. We used three years (2018-2020) of data collected from camera-trap sites (n = 381) in western Kansas, USA to assess multiscale effects of landscape change on the distribution of American badgers (badger, Taxidea taxus), an important predator and ecosystem engineer. We predicted initial site occupancy probabilities and colonization rates would be positively associated with the amount of prairie and Conservation Reserve Program (CRP) hectares surrounding sites. We also predicted site occupancy and colonization would be negatively associated with the amount of row crop agriculture and density of wind towers surrounding sites along with distance to permanent water sources. Habitat use by badgers was insensitive to the amount of prairie and CRP surrounding sites at both local and landscape scales. Contrary to our hypothesis, badgers were more likely to occupy and colonize sites with greater amounts of row-crop agriculture at both landscape and local scales. Additionally, badgers were less likely to occupy sites farther from permanent water sources. Our study suggests that badgers, although considered prairie-obligate carnivores, may be exploiting row crop agricultural areas because of increased prey densities or suitable burrowing/digging substrates. Moreover, our research highlights the importance of permanent water resources to badgers in arid regions within the Great Plains.
Keywords: Agriculture; Camera trap; Carnivore; Great Plains; Landscape change; Occupancy modeling